O ethos institucional da Revista Brasileira para Cegos: as pessoas com deficiência visual como coenunciadores - Deliberal, Sonia Maria (2024)
The present study’s theme is the social representation of people witch visual impairments as coenunciators: from the perspective of de editorialists of the Revista Brasileira para Cegos (RBC). This theme led us to the following questions; What are the social representations of people with visual impairment constructed by the editorialists of Revista Brasileira para Cegos? What are the expressions with qualifying values selected to positively or negatively evaluate the social representation of people with visual impairment? The hypothesis of this research is “The institutional ethos constructed in the RBC editorials, prepared by a representative of the IBC institution, presents a divergence in relation to the editorials prepared by the team under the supervision of the MEC, in the two selected historical moments, regarding the construction of the social representation of people with visual impairment. In order to answer the research questions and enable the affirmation of the aforementioned thesis, the general objective is to: Demonstrate how the institutional ethos constructs the social representation of people with visual impairment in the editorials of the Revista Brasileira para Cegos, and as specific objectives: analyze the institutional ethos of the editorials of the Revista Brasileira para Cegos from the perspective of the Benjamin Constant Institute, from 2000 to 2011; analyze the institutional ethos of the editorials of the Revista Brasileira para Cegos from the perspective of the Ministry of Education and Culture, from 2012 to 2021; compare the results of the two historical periods. To this end, authors who deal with the image demonstrated in the speech through argumentation were chosen as theoretical apparatus in Amossy (2011, 2016, 2017); ethos, including the institutional one in Maingueneau (2007, 2008, 2014); of argumentation, of social representations de Moscovici (1978, 2015), comprising an editorialist and an editorial committee in Goffman (1978, 2008)). In this sense, we also sought to address argumentative operators and articulators, intertextuality and argumentation strategies in Koch & Elias (2021), in addition to the concept of the editorial genre of Van Dijk (1997, 2005, 2007, 2012) Based of the above, we intend to analyze the editorials published in RBC from the perspective of argumentation, social representations and institutional ethos. Ten editorials were analyzed, five from the first period, under the responsibility of editorialist Kate de Queiróz Costa, being: the unnumbered edition, from 2005; number 504, from 2005; number 52, from 2008; number 519, from 2010, and number 524, from 2011. From the second period, under the responsibility of an editorial commission, and also under the influence of the Ministry of Education and Culture, the following editions were selected: number 532, of 2014; number 534, from 2014; number 542, from 2016; number 554, from 2019; e number 556, from 2020. From the results of the analyzes obtained were compared and it was found that, in relation to the first period, the presence of institutional, prior, empirical and affective ethos, which establish a close relationship with your reader; regarding the second, an institutional ethos is perceived as distant and different from its target audience